Mass spectra androgens estrogens other steroids (Wiley, 2005)
The collection contains 2,979 EI mass spectra of androgens and estrogens and their trimethylsily-, O-methoxyoxime- and acetal derivatives. Each spectrum is accompanied by the structure and trivial name, molecular formula, molecular weight, nominal mass and base peak. All spectra of androgens and estrogens have been obtained on the same mass spectrometer under identical conditions.